Sliding Mode Control of Three Levels Back-To-Back VSC-HVDC System Using Space Vector Modulation - Bouafia Saber; Benaissa Abdelkader; Bouzidi Mansour; Barkat Said (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
In this study, a sliding mode strategy proposed to control a three levels Back-to-Back High Voltage Direct Current (HVDC) system based on the three-level voltage source converter (VSC). The voltage-balancing control of two split DC capacitors of the VSC-HVDC system is achieved using three-level space vector modulation with balancing strategy based on the effective use of the redundant switching states of the inverter voltage vectors. Finally, a complete simulation of the VSC-HVDC system validates the efficiency of the proposed strategy law. Compared to the conventional control, Sliding Mode Control scheme for the VSC-HVDC system shows the attractive advantages such as offering high tracking accuracy, fast dynamic response and good robustness.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5575